2019
DOI: 10.3390/rs11030308
|View full text |Cite
|
Sign up to set email alerts
|

Forest Spectral Recovery and Regeneration Dynamics in Stand-Replacing Wildfires of Central Apennines Derived from Landsat Time Series

Abstract: Understanding post-fire regeneration dynamics is an important task for assessing the resilience of forests and to adequately guide post-disturbance management. The main goal of this research was to compare the ability of different Landsat-derived spectral vegetation indices (SVIs) to track post-fire recovery occurring in burned forests of the central Apennines (Italy) at different development stages. Normalized Difference Vegetation Index (NDVI), Normalized Difference Moisture Index (NDMI), Normalized Burn Rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 82 publications
3
45
0
Order By: Relevance
“…Unitless spectral indices can be combined with field survey data to model vegetation cover and other ecosystem traits [72], but it is not clear when such models can be transferred from site to site without additional ground reference data [73]. The NBR correlation with vegetation cover that we observed is similar to the correlation reported by Morresi et al [74], but additional work is needed to validate the consistency of these relationships. Few studies have assessed the ability of NBR and other spectral indices to map fractional cover of vegetation.…”
Section: Remote Sensing Productssupporting
confidence: 49%
See 1 more Smart Citation
“…Unitless spectral indices can be combined with field survey data to model vegetation cover and other ecosystem traits [72], but it is not clear when such models can be transferred from site to site without additional ground reference data [73]. The NBR correlation with vegetation cover that we observed is similar to the correlation reported by Morresi et al [74], but additional work is needed to validate the consistency of these relationships. Few studies have assessed the ability of NBR and other spectral indices to map fractional cover of vegetation.…”
Section: Remote Sensing Productssupporting
confidence: 49%
“…Plots with low burn severity recovered in seven years and plots with moderate burn severity recovered in 13 years. Moressi et al [74] performed a similar analysis using spectral indices. They found that modeled recovery times varied between 8 and 12 years, depending on the forest type, burn severity, and spectral index.…”
Section: Mixed Conifer Forestmentioning
confidence: 99%
“…Moreover, high-resolution canopy-related spectral and ALS-derived attributes were also leveraged by [11] to estimate tree count across canopy cover classes (with r 2 reaching 0.93 when using ALS metrics), whereas medium-resolution but multi-temporal classifications of forest and tree species types by [17] returned promising performances of accuracies >80% by incorporating refinements like topography and stratification. Spectral information from multi-temporal, optical Landsat imagery was also shown by [16] to enable good approximations for forest recovery via the use of multiple vegetation indices, highlighting the tremendous information content within the time series of medium-resolution satellite imagery for monitoring forest stand dynamics on a regional scale and beyond. Finally, [12] followed the important though often underestimated preprocessing step of image co-registration by suggesting a simulated solution based on spatial aggregation over adjacent pixels, which helps with precisely quantifying the co-registration error between the ground control points and satellite data.…”
Section: Summary Of the Published Contributionsmentioning
confidence: 99%
“…Motivated by the recent trends and global interest, the Remote Sensing special issue "Remote Sensing-Based Forest Inventories from Landscape to Global Scale" hosted nine peer-reviewed papers adopting various modern applications of passive and active remote sensing data for multi-scale forest inventory applications. This special issue is enriched with a series of independent, though contextually related, recent studies from diverse geographical domains of the globe, including the near-Arctic Canada [10], Northern United States [11,12], Northern Japan [13], Southern Spain [14,15], Central Italy [16], Southern Poland [17] and Western Germany [18].…”
Section: Summary Of the Published Contributionsmentioning
confidence: 99%
See 1 more Smart Citation